Improving Research And Development Also Technical Projects Using Privities Engineering Schools Competences - Grechi, Roberto; Silveira Luz, Marcio (Revista Ciências Exatas, 2009)
The vast majority of Private Engineering Colleges have a very week, or almost none contact with Industries or Service Providers. This loose relationship has strong negative impacts on all the stakeholders, namely: Industry, College, students, professors and society at large. The basic aim of this work is to highlight and describe what the authors consider as the most relevant causes for this unfruitful behavior, and to present some possible solutions within a methodology framework to overcome the related barriers. Key-words: Research and development. Technical projects. Research in privities engineering schools. Technical projects market. Relationship between schools and companies. Private research institutes.